2018
DOI: 10.23736/s1973-9087.17.04876-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle stretching exercises and resistance training in fibromyalgia: which is better? A three-arm randomized controlled trial

Abstract: The trial included a control group and two intervention groups, both of which received exercise programs created specifically for patients with FM. In clinical practice, we suggest including both modalities in an exercise therapy program for FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 30 publications
5
102
0
Order By: Relevance
“…In addition, other studies compared ST with relaxation or flexibility exercises. Assumpção et al [40] verified the effects of ST and flexibility exercises after 12 weeks of intervention. The results demonstrated that ST is more effective in reducing depression, whereas flexibility exercises are better at improving the quality of life, especially physical function and pain.…”
Section: Kingsley 18 Womenmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, other studies compared ST with relaxation or flexibility exercises. Assumpção et al [40] verified the effects of ST and flexibility exercises after 12 weeks of intervention. The results demonstrated that ST is more effective in reducing depression, whereas flexibility exercises are better at improving the quality of life, especially physical function and pain.…”
Section: Kingsley 18 Womenmentioning
confidence: 94%
“…Of the 22 studies included in the review, the oldest was published in 2001 [38] and the most recent was published in 2017 [24,39,40] (Table 2). Most of the studies were conducted in the United States (36%, n = 8), followed by Finland (23%, n = 5), Brazil (18%, n = 4), Sweden (18%, n = 4), and Turkey (5%, n = 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of 10 was classified as: "the worst pain of lactic acid that you have experienced in your quadriceps." This method has been previously used by Assumpção et al (4).…”
Section: Ratings Of Painmentioning
confidence: 99%
“…Previous studies have shown that exercise interventions based on aerobic exercise or strength can improve pain, depression, physical function, disease impact, and quality of life in women with FM [6][7][8][9][10][11][12][13][14]. Furthermore, exergame interventions (a nonimmersive form of virtual reality) that involve physical exercise [15] have previously been used in patients with FM.…”
Section: Introductionmentioning
confidence: 99%